Commitment to exporting as an antecedent of organizational skills and firm performance - Gonçalves, T.; Teixeira, M. S.; Dias, J. G.; Gouveia, S.; Correia, R. J. (Journal of Business Economics, 2021)
This study proposes the role of leader’s commitment to export activities as an antecedent of specific organizational skills. In particular, this research investigates whether the leaders’ commitment to exporting affects firm performance, through the mediating effect of entrepreneurial orientation, network competence, and dynamic capabilities of a firm, using survey data collected from 976 companies in Portugal. Results from the structural equation model show that leaders’ commitment to exporting, defined as a positive attitude towards the internationalization of their firms, acts as an antecedent of entrepreneurial orientation and network competence. Additionally, we conclude that the relation between this commitment and firm performance is mediated through entrepreneurial orientation, network competence, and dynamic capabilities. This study contributes to the understanding of the mediating effect of these specific organizational skills in the proposed relationship between leaders’ commitment to exporting and firm performance and provides a new insight into the important role of the entrepreneur or top manager.